Social Entrepreneurship and Creative Innovation Ecosystem Implementation - Eljihad Akbari Syukriah Mathory; Murtafia Murtafia; Sudarmi Narwis (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2023)
Social entrepreneurs encourage innovation and social transformation in various fields, including education, health, the environment, and business development. Social entrepreneurs pursued the goal of poverty alleviation,  in the spirit of entrepreneurship, method of business, and courage to innovate and address traditional practices. Entrepreneurial ecosystem, consisting of social policy characteristics such as geography, market share, human resources, cultural factors, and the support of the surrounding community’s social or financial income. The efforts to build an ecosystem are important because there is no certainty or benefit identification for social entrepreneurs. The major obstacle for social entrepreneurs, continuity, is how the existing initiatives can survive and inspire innovation to develop the country. The method used is descriptive qualitative. The research findings showed the social entrepreneur's seventh ecosystem: policy, financial problems, support, Human resources, market empowerment strategy, social network, and geographical location. From this, three creative innovations for scaling up emerged, namely having a more senior mentor, building an organization with partnerships to develop empowerment, and building collaboration with other organizational platforms.